Analgesic Efficacy and Tolerability of Tramadol Versus Low Dose Tramadol-Paracetamol in Patients with Gastro Intestinal Surgery - Nepal, Monica; Paudel, Rama; Poudel, Rajesh; Gautam, Narayan (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Analgesic regimens with an improved efficacy and tolerability balance have potential to improve acute pain management, and thus reduce the progression into chronic pain. Hence, an opportunity was gained to compare analgesic efficacy and tolerability of Tramadol (T) 1.5 mg/kg versus low dose Tramadol 1mg/kg-Paracetamol 1000mg (T-P) in patient with Gastro Intestinal (GI) surgery. MATERIAL AND METHODS: The study was a hospital based prospective, observational study conducted in sixty post-operative GI surgery patient at Universal College of Medical Sciences-Teaching Hospital, Ranigaon, Bhairahawa, Nepal. One group received Tramadol 1.5mg/kg (n=30) while the other group received Tramadol 1mg/kg with Paracetamol 1000 mg (n=30). The primary efficacy outcome measures were pain intensity difference (PID) and sum of pain intensity difference (SPID) whereas secondary efficacy measures included number of patient who require rescue medication, haemodynamic parameter, their quality of sleep in the night and satisfaction with their medication. For tolerability, adverse effect was noted that occurred during study time intervals. RESULTS: Mean pain intensity differences assessed on Numerical Rating Scores (NRS) were significantly better for Group T-P compared to Group T at all the points except 0.5, 1 and 6 hrs. The sum of pain intensity difference over 8, 16, 24, 48 hrs for Group T-P was significantly superior to Group T. Two patients in Tramadol group required rescue medication. Satisfaction to the pain medication was comparatively higher for Tramadol-Paracetamol group. CONCLUSION :- Tramadol-Paracetamol had more pronounced analgesic effect with lower incidence of side effect than Tramadol alone. Thus, low dose Tramadol-Paracetamol is better option for management of post-operative pain in patient with GI surgery.